Mac undercover - Barnett, Mac; Lowery, Mike, 1980- (New York : Orchard Books, 2018)
One day, Mac (smartest boy in his class in a small town in California) receives a telephone call from the Queen of England, recruiting him to find the crown jewels (well, actually just the Coronation Spoon) and so Mac embarks on his first adventure as a secret agent--with the assurance that the Queen will give him a note excusing him from school.
School Library Journal starred, July 2018
Publisher's Weekly, July 2018
Horn Book, September 2018
Bulletin (Center for Children's Books), September 2018
Kirkus Review, June 2018
3.7
Keywords: Undercover operations -- Juvenile fiction; Crown jewels -- Great Britain -- Juvenile fiction; Theft -- Juvenile fiction; Undercover operations -- Fiction; Jewelry -- Fiction; Stealing -- Fiction; Spy fiction; Action and adventure fiction; Humorous fiction